2015
DOI: 10.24059/olj.v19i3.667
|View full text |Cite
|
Sign up to set email alerts
|

Mechanizing People and Pedagogy: Establishing Social Presence in the Online Classroom

Abstract: This research addresses the affordances of using Voki avatars to create a sense of social presence in an asynchronous online writing classroom setting. Digital media afford online educators the opportunity to harness different technologies and new ways of being in a digital classroom that can enhance student engagement in ways similar to yet unlike face-to-face instruction, but this current research questions the effectiveness of these technologies. Original data was obtained from forty students in an online w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…According to the hypothesis, the capacity of different communication channels to transmit social cues influences the degree of social presence felt by participants. When applied to educational contexts, various elements determine the degree of social presence, including communication tools, interaction design, teacher presence, and student-student interactions (Roque-Hernández et al, 2021;Gray & DiLoreto, 2016;Cunningham, 2015). The Community of Inquiry (CoI) concept, developed by Garrison (2016), is another set of theoretical foundations and dimensions of social presence.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…According to the hypothesis, the capacity of different communication channels to transmit social cues influences the degree of social presence felt by participants. When applied to educational contexts, various elements determine the degree of social presence, including communication tools, interaction design, teacher presence, and student-student interactions (Roque-Hernández et al, 2021;Gray & DiLoreto, 2016;Cunningham, 2015). The Community of Inquiry (CoI) concept, developed by Garrison (2016), is another set of theoretical foundations and dimensions of social presence.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…I also recognized how important it was for instructors to establish their own social presence. Cunningham (2015) found that two key components of social presence in an online course are "a present and responsive instructor who can provide relevant feedback . .…”
Section: Experience As An Online Studentmentioning
confidence: 99%
“…As in library instruction, writing instructors have also only recently begun to explore the potential uses of the CoI theoretical framework (Kim, 2016). Much of the work that has been done has focused on specific presences within the CoI theoretical framework as these relate to first-year writing courses: social presence (Cunningham, 2015;Lomicka & Lored, 2012), teaching presence (Docker, 2016;Grigoryan, 2017) and cognitive presence (Comer, Clark, & Canelas, 2014). Other studies look at all three presences in relation to providing online feedback (Cox, Black, Heney, & Keith, 2015;Yang, 2016).…”
Section: Connecting the Community Of Inquiry Theoretical Framework Tomentioning
confidence: 99%